Taking advantage of water scarcity? Concentration of agricultural land and the politics behind water governance in Chile - Perez-Silva, Rodrigo; Castillo, Mayarí (Frontiers in Environmental Science, 2023)
Chile is currently facing a major drought that has caused several problems, most of them concentrated in terms of the availability of water for both human consumption and irrigation for agriculture. Under such conditions, the main instrument the government has at hand to assign water for agricultural use is the Water Scarcity Decree (WSD), which, among other aspects, allows for the extraction of underground water. However, this practice requires an important investment from the agricultural producer, making it only affordable by relatively larger producers. Therefore, under the current climatic conditions and a generalized lack of water, larger agricultural producers are the ones who benefit the most from the establishment of a WSD and thus have the incentives to use their political power to pressure for its issuing. Whereas conventional wisdom suggest that this is indeed the case, there is no previous evidence trying to link the size of agricultural exploitations and the likelihood of the establishment of a WSD. In the paper we use the share of large exploitations at the municipality level, as a measure that can proxy for local political power, and the establishment, the number, and duration of WSD within any given year. Consistent with the hypothesis, our results show that areas dominated by larger producers/exploitations are more likely to be declared as water scarce, to have more decrees in a year, and to have them in place for longer periods of time, even after controlling for socioeconomic characteristics and climatic conditions, such as precipitations and water flow.